Yukon ho! : a Calvin and Hobbes collection - Watterson, Bill (Watterson, Bill. Calvin and Hobbes collection., 1989)
Calvin--a six-year-old boy with a boundless imagination and a zest for misadventure--confounds his parents, his teacher and his classmates with the help of his lovable stuffed tiger Hobbes.